Agency theory and corporate monitoring : evidence from developing country. - Mustapha, Mazlina
Monitoring mechanisms that are mandatory for Malaysian public listed companies are internal auditing, external auditing and directorship. There is a comparative advantage of each type of these mechanisms and they complement each other. It is claimed that the attributes of an organisation can influence its monitoring costs, as the costs are the function of the systems adopted by the organisation. This is important as the costs involve may jeopardise the shareholders wealth and future survival of the organisation. Thus, this research investigates the impacts of these organisational attributes on the demands of these three monitoring mechanisms among Malaysian public listed companies. The organisational attributes that are examined are ownership structure, debt structure, information system structure, compensation structure, multinational status and ethnicity. The results of this study provide evidence that are consistent to agency theory; managerial shareholdings and debt structure appear to have negative significant relationships with monitoring costs. However, another ownership variable seems to give different finding compared to those studies in western countries. Block-holders appear to demand more monitoring costs, which may be due to the concentrated business environment in Malaysia. Other organisational attributes which are significant in its association with monitoring costs are multinational status and ethnicity.